2002
DOI: 10.3758/bf03194952
|View full text |Cite
|
Sign up to set email alerts
|

Proust nose best: Odors are better cues of autobiographical memory

Abstract: The Proust phenomenon is an enduring piece of folk wisdom that asserts that odors are particularly powerful autobiographical memory cues. We provide a more formal exposition of this phenomenon and test it in two experiments, using a novel double-cuing methodology designed to negate less interesting explanations. In both studies, recall of an autobiographical event was initially cued by a verbal label (an odor name) for a fixed period, following which a second, extended recall attempt was cued by the same verba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
153
2
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(176 citation statements)
references
References 31 publications
8
153
2
7
Order By: Relevance
“…The results of this study support the notion that olfactory evoked memories are more emotional than memories evoked by verbal cues (Chu & Downes, 2002;Herz, 2004;Herz & Cupchik, 1995). As noted above, evidence is equivocal regarding whether it is the memory by itself that is more emotional or whether it is the perceptual properties of the olfactory cue that produce the higher emotional arousal.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The results of this study support the notion that olfactory evoked memories are more emotional than memories evoked by verbal cues (Chu & Downes, 2002;Herz, 2004;Herz & Cupchik, 1995). As noted above, evidence is equivocal regarding whether it is the memory by itself that is more emotional or whether it is the perceptual properties of the olfactory cue that produce the higher emotional arousal.…”
Section: Discussionsupporting
confidence: 64%
“…Because passive smelling of odors may influence the emotional arousal in individuals (e.g., Lehrner, Marwinski, Lehr, Johren, & Deecke, 2005;Savic et al, 2000), without memory recollection, it is of interest to investigate the role played by olfactory perception in the recollection and phenomenological evaluation of retrieved memories (cf. Chu & Downes, 2002;Herz & Schooler, 2002). …”
mentioning
confidence: 99%
“…It also crucially expands consideration of the crossmodal associations elicited by olfactory cues beyond the idiosyncratic evocations studied as the "Proust phenomenon" (e.g., Chu & Downes, 2002;Willander & Larsson, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…The final section concludes with two arguments related to seeking a better understanding of the crossmodal correspondences holding between contingent features, such as those holding between smells and auditory or shape features: First, researchers should resist the idea that the associations are merely anecdotal, but rather should subject them to systematic investigation (see also Stevenson et al, 2012). Second, we propose an alternative framework to investigate the most surprising cases of crossmodal associations, one that contrasts with their being seen as either synesthetic connections (an interpretation that was suggested for smelltaste associations by Stevenson & Tomiczek, 2007, and is easily extended to crossmodal associations between smell and musical notes) or merely grounded in episodic memories (as has been proposed to explain "Proustian" associations between odors and visual images; see Chu & Downes, 2002;Willander & Larsson, 2006.…”
mentioning
confidence: 99%
“…[17]. Many studies focused on the ability of olfactory stimuli, compared to stimuli of other senses, to recall people's memories about their lives, experiences, places, people, events, and also smells experienced long time ago [18]. Moreover, Herz [19] demonstrated that memories triggered by smells are considered as more emotional than those evoked by the other types of stimuli.…”
Section: Related Workmentioning
confidence: 99%